Comparative evaluation of bioactive glass bone graft material with platelet rich fibrin and bioactive glass bone graft material alone for the treatment of periodontal intrabony defects: a clinical and radiographic study - Ashawan, Prashant John; Zade, R. M. (International Journal of Research in Medical Sciences, 2017)
Background: The primary goal of periodontal therapy is to arrest the progression of periodontal disease and maintain the natural dentition in health and comfortable function. Growth factors that seem to play an important role in periodontal and bone wound healing are PDGF, IGF combined with PDGF and TGF-ß. Platelet-rich fibrin (PRF) seems to be an appropriate and economical method to obtain these growth factors. The cell type-specific actions of PRF may be beneficial for periodontal regeneration. The purpose of this study is to compare the clinical and radiographic outcomes obtained by a combination of bioactive glass with PRF and bioactive glass alone in treatment of periodontal intrabony defects. Methods: The present study was carried out in Rajnandgaon city (C.G.) India, during study period May 2013 to October 2014. After initial examination, the following recording was made using Plaque index and Gingival index. Preparation of PRF was done by Choukroun criteria. Surgical procedure was performed. Post-surgical findings were noted. Student t test (Paired and unpaired) were applied with value of <0.05 was considered statistically significant for interpretation of finding. Results: The mean probing pocket depth, clinical attachment level and bone level for the Test group at baseline were 7.45mm with S.D±1.38, 9.9.mm with S.D±1.32 at 3 month and 6.45 mm with S.D±1.53 mm at 6 month. (Significant p<0.0001) Similar significant findings were also noted in control group. Conclusions: The study showed significant improvements in clinical and the radiographic parameters in each group.